Secondary antibody deficiency is associated with development of infection in kidney transplantation: Results of a multicenter study. Issue 2 (27th October 2020) - Sarmiento, Elizabeth; Jimenez, Maricela; di Natale, Marisa; Rodriguez‐Ferrero, Marisa; Anaya, Fernando; Lopez‐Hoyos, Marcos; Rodrigo, Emilio; Arias, Manuel; Perello, Manel; Seron, Daniel; Karanovic, Boris; Ezzahouri, Ikram; et al.
Abstract: Background: We performed a multicenter study to assess the association between secondary antibody deficiency (immunoglobulin G [IgG] hypogammaglobulinemia combined with low levels of specific antibodies) and development of infection in kidney transplantation. Methods: We prospectively analyzed 250 adult kidney recipients at four centers. The assessment points were before transplantation and 7 and 30 days after transplantation. The immune parameters were as follows: IgG, IgA, and IgM and complement factors C3 and C4 tested by nephelometry; specific IgG antibodies to cytomegalovirus (CMV) and IgG and IgG2 antibodies to pneumococcal polysaccharide (anti‐PPS) determined using enzyme‐linked immunosorbent assay. The clinical follow‐up period lasted 6 months. The clinical outcomes were CMV disease and recurrent bacterial infections requiring antimicrobial therapy. Statistics: Multivariate logistic regression. Results: At day 7, IgG hypogammaglobulinemia (IgG levels < 700 mg/dL) combined with low IgG anti‐CMV antibody titers (defined as levels < 10 000 units) was present in 12% of kidney recipients. IgG hypogammaglobulinemia combined with low IgG anti‐PPS antibody titers (defined as levels < 10 mg/dL) at 1 month after kidney transplantation were recorded in 16% of patients. At day 7 the combination of IgG hypogammaglobulinemia and low anti‐CMV titers was independently associated with the development of CMV disease (odds ratio [OR], 6.95; 95% confidence interval [CI], 1.17‐41.31; P = .033). At day 30 after transplantation, the combination of IgG < 700 mg/dL and IgG anti‐PPS < 10 mg/dL, was independently associated with recurrent bacterial infection (OR, 5.942; 95% CI, 1.943‐18.172; P = .002). Conclusion: In a prospective multicenter study, early immunologic monitoring of secondary antibody deficiency proved useful for the identification of kidney recipients who developed severe infection.